SOCIOPRENEUR IN DIGITAL MARKETING: EMPOWERING THE MICRO, SMALL AND MEDIUM ENTERPRISES (MSMES) IN BOJONGPICUNG VILLAGES - Mardian, Vivi; Yakin, Husnul; Azzahra, Waliyyatu; Nuraini; Fadhlan Nabil , Ziyad (Jurnal Layanan Masyarakat (Journal of Public Services), 2024)
The Indonesian economy is largely derived from Micro, Small and Medium Enterprises (MSMEs). The MSME sector has a strategic role in the Indonesian economy because it is significant in contributing to the formation of Gross Domestic Product (GDP). However, Small and Medium Enterprises (SMEs) tend to not keep up with the development of digital technology, mainly due to a lack of knowledge about digital marketing. Therefore, the Postgraduate Muslim Student Association (HIMMPAS) of Universitas Pendidikan Indonesia conducted training through social entrepreneurship activity in Bojongpicung Village and Jati Village, Cianjur Regency, West Java. This training aimed to provide insight to MSME practitioners by optimizing the potential of MSMEs through digital marketing to improve the economy of the local community in Bojongpicung Village and Jati Village, Bojongpicung District, Cianjur Regency, West Java. The MSME participants involved in this training totaled 11 people from various industries. This program applied direct training and mentoring methods. The discussion in this article aimed to identify constraints or problems experienced by the MSMEs and evaluate the participants' level of satisfaction with the implementation of the training activities. The results showed that MSME participants have constraints in product marketing, funding, and traditional production equipment. After being trained, MSME participants found several relevant solutions for the development of their MSME businesses through digital marketing. In addition, the material provided was in accordance with the needs of MSME participants. MSME participants also realized that they still need more similar training in the future.